Perceived stress and demographic characteristics of women with multiple sclerosis - Bastani, F; Hakimi Gilani, T; Ghane-fard, Shadi; Ghane-fard, Shirin (Advances in Nursing & Midwifery, 2010)
Background and aim Multiple sclerosis (MS) is a neurologic, chronic and progressive disease in which stress and stressful events may play as a trigger in the occurrence and relapse of its symptoms. With respect to higher incidence of MS in women, the aim of this descriptive study was to determine perceived stress and demographic characteristics of women with symptomatic MS. Materials and Methods Subject population consisted of all women with signs and symptoms of MS referring to Association of MS patients or one of the hospitals affiliated to Iran, Shahid Beheshti and Tehran Medical Universities. A consecutive sampling method was used to select 190 women. A demographic questionnaire and Perceived Stress scale (PSS) were used for data collection. Although the scale was psychometrically evaluated in previous Iranian studies, content and Cronbach’s α methods were used for the validity and internal consistency of it respectively. For quantitative analysis, different descriptive statistical methods were applied for data analysis. Findings Most women (mean age=33.6) were married (63.5%) with high school diploma or academic education (75.7%) and household (65.8%) in middle class (76.7%). Mean duration of affliction was 5 years with at least 1 period of hospitalization and often with no social support (79.8%). In addition, more than half of them (53.7%) had high perceived stress and the rest experienced low stress. Conclusion According to the study results and with respect to probable role of stress in triggering or relapsing MS signs and symptoms, more extensive studies are deemed necessary to identify stressful factors. In addition, by considering the lack of social support and high perceived stress in most subjects and changeability and modifiability of these variables, providing facilities for instruction and consultation to support the patients and manage their stress is recommended. Keywords: Perceived stress, Multiple sclerosis, Women’s health, Social support, Mental health. *Corresponding Author: Bastani, Farideh. Assistant Professor, Dept. of Health, Faculty of Nursing and Midwifery, Iran University of Medical Sciences, Tehran, Iran. E-mail: fbastani@inms.ac.ir